Family Profile of Substance Addicted Individuals - Fatmanur Alsancak; Hülya Yıldız; Hüseyin Zahid Kara; Hasan Hüseyin Taylan; Yusuf Genç (Skad)
Today, substance use and related risks are increasing day by day, and the influence of the family on substance addiction is important. Studies show that the socioeconomic characteristics, structure, and relationship patterns between family members and substance use affect the families of substance addicted individuals in various ways, that the attitude and behavior of the family towards the substance are effective in the substance use of individuals, especially in adolescence, or that the breakdown of the family for various reasons is effective in the orientation of individuals towards substance use. The presence of a substance addicted member in the family negatively affects the functioning and health of the family. In this study, the profiles of the families of substance addicts living in Sakarya were revealed by adopting a descriptive screening model, and it was aimed to make some concrete suggestions about this by examining the effects of family characteristics on addicted people. Accordingly, 147 people who reside in Sakarya and have substance addicted family members were reached by snowball sampling and survey questions were asked. The data obtained were analyzed with basic statistics and chi-square tests in the SPSS program. According to the findings obtained from the research, it was observed that the economic level of the families of substance addicted individuals was at the lower-middle income level, they did not have regular income, they were the middle-aged, there was no one in the family who had used drugs before, and family relationships and communication were positive. Families think that peer influence is highly effective in substance addiction. When families learn that the addicted person is using drugs, they are shaken economically and psychologically and experience a loss of social reputation. It is noteworthy that family members trained on substance addiction are highly aware of addiction and have a hortative attitude towards the addicted individual.